Gods of Management / The Changing Work of Organisations - Handy Charles (Arrow, 1995)
This book is a world bestseller which is required reading for managers, business students and everyone who wants to be a survivor in a world of constantly changing organizational culture. Introduction, The Theory of Cultural Propriety, The Four Gods of Management, The Gods at Work, The Gods in Balance, The Gods in Their Settings, The Apollonian Crisis, The Dilemma of Apollo, Reactions, The Gods in New Order, The Consequences, Notes and References, Index.